The concept of robusticity in (palaeo-) anthropology and its broad range of application: a short review - Tony Chevalier (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The concept of robusticity is widely used in palaeoanthropological and bioarchaeological studies. Distinct skeletal structures are described as robust. Many specialists and non-specialists alike use the term robusticity colloquially to emphasize a general impression, sometimes without considering all the specific definitions it may encompass. Structural robusticity generally refers to a strong or heavy structure, and to the ability of bone structure to resist loads. A wide variety of quantitative and qualitative criteria are used to determine structural robusticity. For example, some authors evaluate bone hypertrophy/reinforcement from a biomechanical approach, and scaled variables based on body size or baseline load; other authors refer to crests, tori, ridges and rugosities. The disparately used term robusticity also includes criteria representing nothing more than bone size (i.e., non-scaled variables) and shape. Consequently, the term robusticity (or robust, robustness) must be used with care, specifically in syntheses and by non-specialists.